Rancang Bangun Mesin Press dan Dryer Untuk Meningkatkan Kekuatan dan Nilai Estetika Parket Sabut Kelapa Berlaminasi - Sujana, Ivan; Prawatya, Yopa Eka; Wardenaar, Evy (ELKHA : Jurnal Teknik Elektro, 2014)
Abstract– This research aimed to improved parquet of coconut coir through improvement the esthetics of the parquet coconut coir with extendlaminate tekstur using substance of environment waste that assumed unused for society but have potency to be used like for example husk of bamboo bar, so that can produce parquet of coconut coir laminate withnatural tekstur.Method used for the process of coconut coir become the parquet laminate is beforehand by using cold press and hot press to produce result the parquet coconut coir, furthermoreproduce of raw material for the lamination tekstur that coming from waste of like bamboo bar which then will applied at parquet of coconut coir through press processing and draining with the system of warm-up infrared.This research aimed to design and construct the press and dryer machine to produce parquet laminate from coco fiber in accordance with the Indonesian National Standard (SNI 01-4449-2006). Researchers conducted a factorial experiment on the composition of the material forming the parquet laminate to have been a factor in the study of high density < 0.84 g/cm3 and medium density factor is 0.40g/cm3 to 0.84 g/cm3. Based on the test results of density, parquet laminate generated by the composition of 50% coco fiber with 50% adhesive and filler classified as High Density Fiberboard and parquet laminate with composition of 65% coco fiber with a 35% mixture of adhesive and filler classified as Medium density Fiberboard. Based on tests of water absorption and water content, parquet laminate with a composition of 35% coco fiber with 65% adhesive and filler or parquet with composition of 50 % coco fiber with 50 % adhesive and filler has been able to meet the requirement. Based on the thick expansion test, only parquet with code C3-IK6 and C3-IK9 qualified to the category of medium density fiberboard. Based on the tensile test perpendicular surface firmness, parquet printout for the composition 35 % coco fiber with 65 % adhesive and filler, and the composition of 50% coco fiber with 50% adhesive and filler has a surface perpendicular firmness pull more than 1.5 kgf/cm2 thus meeting the requirements. Based on the constancy test flexural fracture (MOR) and modulus of elasticity firmness (MOE), test of parquet in this research meet the requirements of SNI No. 01-4449-2006 to the category of medium density fiberboard Type 15. Keywords– parquet, laminate, press and dryer